Genetic analysis of the brahma gene of Drosophila melanogaster and polytene chromosome subdivisions 72AB. - Brizuela, B.J.; Elfring, L.K.; Ballard, J.; Tamkun, J.W.; Kennison, J.A. (Genetics, 1994)
The brahma gene is required for activation of the homeotic genes of the Antennapedia and bithorax complexes in Drosophila. We have isolated and characterized 21 mutations in brahma. We show that both maternal and zygotic functions of brahma are required during embryogenesis. In addition, the severe abnormalities caused by loss of maternal brahma expression show that the homeotic genes are not the only targets for brahma activation. The complex pattern of interallelic complementation for the 21 brahma alleles suggests that brahama may act as a multimer. In addition to mutations in brahma, we have isolated mutations in four other essential genes within polytene chromosome subdivisions 72AB. Based on a compilation of similar studies that include about 24% of the genome, we estimate that about 3600 genes in Drosophila can mutate to cause recessive lethality, with fewer than 900 additional genes essential only for gametogenesis. We have identified three times more transcripts than lethal complementation groups in 72AB. One transcript in 72AB is the product of the essential arf-like gene and encodes a member of the ARF subfamily of small GTP-binding proteins. Two other transcripts are probably the products of a single gene whose protein products are similar to the catalytic subunits of cAMP-dependent protein kinases.